PO194 Reversible atypical amsan like presentation in a patient with cmml, is it paraneoplastic or simply an autoimmune disorder?. (1st December 2017) - Connon, Paul; Hywel, Brython; Bonello, Michael; Ellul, Mark; Manohar, Radhika; Holt, James; Toth, Arpad; Alusi, Sundus
Abstract : Chronic myelomonocytic leukaemia (CMML) is a malignant haematopoietic stem cell disorder. Autoimmune disorders including demyelinating Guillain-Barre Syndrome (GBS) have been rarely described in association, but monophasic reversible axonal polyneuropathies have not. We report a 64 year old man who presented with 8 weeks of progressive leg weakness, paresthesia of the hands and feet, and weight loss. He was diagnosed with CMML the preceding year during investigations for cutaneous vasculitis. Examination revealed symmetrical lower motor neuron weakness, distal in the arms; proximal in the legs. Sensory loss to all modalities was present. CSF analysis confirmed albumin-cytological dissociation. No infiltration was seen on contrast imaging of the neuroaxis. Nerve conduction studies showed no evidence of demyelination, but an axonal sensori-motor polyneuropathy. He deteriorated rapidly with widespread denervation and respiratory involvement. Steroids and IV immunoglobulins did not help but improvement started after 1 cycle of intermediate dose ARA-C chemotherapy followed by hydroxycarbamide. There was a transient recovery of FBC abnormalities but the CMML picture returned. After neurological rehabilitation he made a full functional recovery. Monophasic axonal polyneuropathies can be associated with CMML and can respond to chemotherapy. The exact pathophysiological immunomodulatory mechanism is unclear. Prompt recognition and treatment can result in excellent recovery.